A história do intemperismo na Província Borborema Oriental, Nordeste do Brasil: implicações paleoclimáticas e tectônicas - Lima, Maria da Guia (2008)
Until some years ago, weathering geochronology was primarily based on the K-Ar and 40Ar/39Ar dating of supergene minerals. Recent advances in the analysis of supergene goethite by the (U-Th)/He method expanded the number of suitable minerals for such purpose, as well as the time of application for weathering geochronology. This study represents the first systematic approach in Brazil, combining both the 40Ar/39Ar e (U-Th)/He methodologies to improve the knowledge on the weathering and the age of nonfossiliferous sediments. Supported by geologic and geomorphologic correlations, we identified different types of weathering profiles occurring in the interior and coastal areas of northeastern Brazil. These profiles were correlated to main regional geomorphological domains: the Borborema Plateau , the Sertaneja Depression , and the Coastal Cuestas and Plains, and respective planation surfaces, which study is fundamental to understand the landscape evolution of the northern portion of the eastern Borborema Province. The depth and stratigraphic organization of the weathering profiles in each of the geomorphological domains permitted to establish that: (i) the profiles on the highlands that cap the Borborema Surface are deeper (up to 100 m) and can be considered as typical lateritic profiles; (ii) on the lowlands that form the Sertaneja Surface , the weathering profiles are shallow and poorly developed (2-5 m deep); (iii) the profiles along the coastal area are moderately developed (up to 25 m deep), and are characterized by thick saprolites and mottle zones. Aiming to establish the timing of the evolution of northeastern Brazil, we studied 29 weathering profiles representing distinct topographic levels of the Borborema Province, from the highlands to the coast, through the analysis of 248 grains of supergene manganese oxides using laser step-heating 40Ar/39Ar geochronology. Additionally, we applied the (U-Th)/He method in 20 weathering profiles, by dating 171 grains of supergene iron oxides and hydroxides. Geochronological results for 248 grains of manganese oxides analyzed by the 40Ar/39Ar method indicate that the weathering profiles in the study area record the history of weathering from the Oligocene to the Pleistocene, with ages in the order of 31.4 ± 1.0 Ma to 0.8 ± 0.4 Ma. Dating of 171 grains of goethite by the (U-Th)/He method yielded ages ranging from 43.2 ± 4.3 Ma to 0.8 ± 0.1 Ma, suggesting the weathering processes last from the Eocene to the Pleistocene. The precipitation of supergene goethite in this interval confirms the age of the weathering processes identified from the manganese oxides record. 105 goethite grains from 8 different occurrences of the Barreiras Formation were dated by the (U-Th)/He method. Five grains collected from the cement in the Barreiras Formation sandstones, in the Lagoa Salgada and Rio do Fogo coastal cuestas, yielded ages of 17.6 ± 1.8 Ma, 17.3 ± 1.7 Ma, 16.3 ± 1.6 Ma, 16.2 ± 1.6 Ma and 13.6 ± 1.4 Ma. Results of 69 goethite grains from authigenic pisoliths collected in 7 different localities also yielded concordant ages, varying from 17.8 ± 1.8 to 7.5 ± 0.8 Ma. Results obtained from 31 detrital grains are concordant in 3 distinct localities (Lagoa Salgada, Praia da Garças e Ponta Grossa); they vary in the range of 43.2 ± 4.3 to 21.6 ± 2.2 Ma, and indicate that the maximum age for the Barreiras Formation deposition is around 22 Ma. 40Ar/39Ar results for 15 manganese oxides grains associated with the Barreiras Formation weathering profiles, in 3 different localities, vary from 13.1 ± 0.9 to 7.7 ± 0.4 Ma, in the same range of ages obtained by the (U-Th)/He method. The systematic application of the 40Ar/39Ar and (U-Th)/He methods, respectively for manganese oxides and goethites, show that the Barreiras Formation sediments were already deposited since ca. 17 Ma, and that the weathering processes were active until ca. 7 Ma ago. The ages obtained from manganese oxides collected in the Cenozoic basalts (Macau Formation) also reveal a weathering history between 19 and 7 Ma, pointing to hot and humid conditions during most of the Miocene. 40Ar/39Ar ages yielded by manganese oxides associated with the Serra do Martins Formation vary from 14.1 ± 0.4 to 10.5 ± 0.3 Ma. On the other hand, (U-Th)/He ages from iron oxides/hydroxides collected in the Serra do Martins Formation mesas vary from 20.0 ± 2.0 to 5.5 ± 0.6 Ma, indicating that those sediments are older than 20 Ma. 40Ar/39Ar and (U-Th)/He results produced in this study are in agreement with paleoclimatic interpretations based on stable isotopes and clay index values measured in the Atlantic Ocean sediments, validating the use of weathering geochronology to investigate paleoclimatic variations. The direct dating of the Barreiras Formation permitted, for the first time, confident inferences on the age of the brittle deformation recorded by this sedimentary unit in the Rio Grande do Norte and Ceará states. The first event, syn-deposition, occurred during the early Miocene; an younger event, related to the post-depositional deformation of the Barreiras Formation, is associated with tectonic activity from the very early Miocene to the Holocene. In agreement with data from other areas, results obtained in this study reveal that the depth and complexity of the weathering profiles reflect the time of exposition of such areas to the weathering agents close to the surface. However, there is no clear relationship between ages vs. altitude. The depth and the stratigraphic organization of weathering profiles in northeastern Brazil, contrary to the southeastern Brazil pattern, do not vary toward the coast. In our study area, field observations reveal the presence of ancient, thick and complex lateritic profiles preserved in the sedimentary mesas on the Borborema Plateau, as younger, narrow and incipient ones occur in the dissected areas. Geochronological results obtained for these profiles yielded older ages on the high altitudes, and younger ages in the lowlands, suggesting the scarp retreatment is the most reliable model to explain the regional landscape evolution. However, in the coastal lowlands, the relatively older ages obtained indicate that more complexes processes were involved in the modeling of the local relief